DEPICTION OF THE CLOTHING AND ATTRIBUTES OF SAINTS IN THE ICONOGRAPHY OF THE LEFT-BANK UKRAINE AND KYIV REGION IN THE SECOND HALF OF THE 17TH – FIRST HALF OF THE 18TH CENTURY - Хребтенко, М. С. (Art and Design, 2020)
To identify and analyze ways of depiction of clothing in the iconography of the Left Bank Ukraine and Kyiv region in the second half of the 17th - the first half of the 18th centuries. The author conducted a field exploration of painted icon monuments from the mentioned period in the collections of Ukrainian museums. The data obtained was supplemented with information from published scientific papers and archival sources. The analysis performed made it possible to trace the peculiarities of the depiction of different fabrics in the iconography of the Left Bank Ukraine and Kyiv region in the second half of the 17th – first half of the 18th centuries, and to identify the aspects of the effects on it of Byzantine and Western European painting techniques. It is revealed that in the Ukrainian icon painting till the end of the 17th century was used a method for depicting fabrics, whose roots go back to the Byzantine system of tempera painting. Although white levkas remained dominant in Ukrainian iconography, by the beginning of the 18th century masters could tone grounds and make imprimaturas, which had their influence on the process of painting clothing and the icon in general. Since about the second quarter of the 18th century the use of grisaille underpaints has been encountered in some icons. These innovations demonstrate the impact of Western European painting at the technical and technological level. Gold and silver were widely used for decorating icons. In that time to decorate the icons were widely used leaf gold and silver and powdered gold and silver. For the first time, the subject of research is the process of painting the garment part of the icons of Left-Bank Ukraine and the Kiev region in the second half of the XVII - the first half of the XVIII centuries. The methods of depicting clothing and common techniques for decorating and depicting texture of fabrics are described and analyzed in detail. The study expands knowledge about Ukrainian icon painting and reveals the technique of its creation.